Advertisement Remove all ads

Solve: X4 – 2x2 – 3 =0 - Mathematics

Sum

Solve:
x4 – 2x2 – 3 =0

Advertisement Remove all ads

Solution

`x4 – 2x2 – 3 =0

`=> x^4 - 3x^2 + x^2 - 3 = 0`

`=> x^2(x^2 - 3) + 1(x^2 - 3) = 0`

`=> (x^2- 3)(x^2 + 1) = 0`

if `x^2 - 3 = 0`   or  `x^2 + 1 = 0`

`=> x^2  = 3 or x^2 = -1`(reject)

`=> x = +-sqrt3`

  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×